Helicobacter pylori infection in pet animals in Suez Canal area and their public health significance - Enany, Mohamed El-S.; Khafagy, Ahmad A.; Mohamed, Nader Atia.; Ibrahem, Ahmad A. H. (2004)
A total number of 50 stool, 50 saliva and 50 serum samples were collected from 50 cats, 50 dogs and 50 owners from hospital of pet animals in port-Said governorate. As well as 23 stomach samples were collected from domestic cats recently euthanized in port-Said governorate. In addition 20 samples from human subjects suffering from dyspepsia, nausea, vomiting, and abdominal pain were collected. Specimens were subjected to bacterial isolation by culture and biotyping, ELISA and PCR to detect UreC subunit of urease gene. Endoscopic examination of 20 human subjects including normal and with gastritis, gastric ulcer and duodenal ulcer represented of 10%, 30%, 50% and 10%, respectively. Among them, 75% were H. pylori +ve by rapid urease test (RUT), 60% were H. pylori +ve by culture and 80%were +ve by ELISA.
Includes references.
Summary in Arabic.
1
Keywords: Dogs -- Diseases; Cats -- Diseases; Helicobacter pylori infections